Spatial occurrence records and distributions of tropical Asian butterflies - Yau, Eugene Yu Hin; Emily E. Jones; Tsang, Toby Pak Nok; Shuang Xing; Richard T. Corlett; Patrick Roehrdanz; David J. Lohman; Lee, Adam Kai Chi; Hai, Catherine Wai Ching; Shawan Chowdhury; Jane K. Hill; Jade A. T. Badon; et al. (Springer Nature, 2025)
Insect biogeography is poorly documented globally, particularly in the tropics. Recent intensive research in tropical Asia, combined with increasingly available records from citizen science, provides an opportunity to map the distributions of tropical Asian butterflies. We compiled a dataset of 730,190 occurrences of 3,752 tropical Asian butterfly species by aggregating records from GBIF (651,285 records), published literature (27,217), published databases (37,695), and unpublished data (13,993). Here, we present this dataset and single-species distribution maps of 1,576 species. Using these maps, along with records of the 2,176 remaining species, we identified areas of limited sampling (e.g., Myanmar and New Guinea) and predicted areas of high diversity (Peninsular Malaysia and Borneo). This dataset can be leveraged for a range of studies on Asian and tropical butterflies, including 1) species biogeography, 2) sampling prioritization to fill gaps, 3) biodiversity hotspot mapping, and 4) conservation evaluation and planning. We encourage the continued development of this dataset and the associated code as a tool for the conservation of tropical Asian insects.